Islamic Boarding School Marketing Communication and Da'wah Through Tik-Tok - Isnaini, Muhammad; Fauzi, Ahmad (Dakwah, 2022)
Marketing communication is a means of informing, persuading, and reminding consumers directly or indirectly about the products and brands being sold. In the context of this research, marketing communication is carried out with regard to the service products offered by the Asy-Syarifiy Islamic boarding school. In particular, that is done through the Tik-Tok social media account. Because it is classified as an Islamic educational institution, in each stage of marketing communication, there are nuances of preaching that are delivered. Da'wah and marketing communications are the focus of research in this article. The Tik-Tok account analyzed is @Kingzadma which belongs to the boarding school caregiver. The purpose of this study is to describe the da'wah model and marketing communication strategy of the Asy-Syarifiy Islamic boarding school through social media Tik-Tok @Kingzadma. This study uses a qualitative method. Data collection techniques using interviews, observation and documentation. Based on the results of the research, it is known that the da'wah model and marketing communication strategy carried out by the Tik-Tok @Kingzadma account uses four elements, namely, entertainment, interaction, trendiness and customization. Da'wah and marketing communications are carried out through the exploration of these four elements. Entertainment is everything in the form of words, places, objects, behaviors that can be comfort or consolation for a difficult or sad heart. Interaction is a meeting between a person and another individual. Trendiness is the ability to browse trending content on Tik-Tok and adapt it to your own content. Customization is a presentation in a video or video display to make it more interesting.